Impact of riverbed topography on hydrology in small watersheds using Soil and Water Assessment Tool. (June 2022) - Kim, Deok-Woo; Chung, Eu Gene; Kim, Kyunghyun; Kim, Yongseok
Abstract: In various watershed-based hydrological models, river topography information is generated by utilizing empirical expressions developed for large catchments. Therefore, identified the impact of channel geometry factors on hydrologic simulation in small watersheds and evaluation of reproducibility of river flow rate are required. We applied the Soil and Water Assessment Tool (SWAT) to small agricultural watersheds and compared measurements obtained from a river with DEM-generated values. The channel geometry factors determined using DEM were underestimated in comparison with measurements; however, using the measured channel geometry as the model input led to a 14.7% increase in the R 2 and Nash–Sutcliffe coefficient (NSE) values in the daily average flow. In addition, the R 2 and NSE values were more accurate by approximately 26% and 47% than the DEM-based optimized values obtained through SWAT-Calibration and Uncertainty Program (CUP)/Sequential Uncertainty Fitting ver.2 (SUFI-2) optimization, based on measured riverbed topography. Highlights: SWAT was applied to a small agricultural watershed considering riverbed topography. The riverbed topography obtained from a river was compared with the DEM-generated. Model evaluation showed high accuracy for the measured riverbed topography. Channel geometry factors are sensitive on daily hydrological simulation for small watersheds.